Case Report: Aicardi-Goutières Syndrome Caused by Novel TREX1 Variants - Wu, De; Fang, Liwei; Huang, Ting; Ying, Songcheng (Frontiers in Pediatrics, 2021)
TREX1 (Three Prime Repair Exonuclease 1) gene encodes DNA 3' end repair exonuclease that plays an important role in DNA repair. Mutations in TREX1 gene have been identified as the cause of a rare autoimmune neurological disease, Aicardi-Goutières syndrome (AGS). Here, we report an AGS case of 6-month-old Chinese girl with novel TREX1 variants. The patient had mild rashes on the face and legs, increased muscle tensions in the limbs, and positive cervical correction reflex. Cranial magnetic resonance imaging (Cranial MRI) showed that there were patches of slightly longer T1.T2 signals in the bilateral cerebral hemisphere and brainstem white matter, mainly in the frontotemporal lobe, together with decreased white matter volume, enlarged ventricles, and widened sulcus fissure. Total exon sequencing showed that the TREX1 gene of the child had mutations of c.137_138insC and c.292_293insA, which had not been reported before. In addition, elevated type I interferons were detected by using ELISA in the patient’s serum. Together, our study demonstrated that novel TREX1 variants (c.137_138insC and c.292_293insA) cause AGS for the first time.